2022
DOI: 10.33003/6fjs-2022-0504-1016
|View full text |Cite
|
Sign up to set email alerts
|

INTESTINAL PARASITIC FAUNA AND PREVALENCE IN AFRICAN GIANT RAT (Cricetomys gambianus) IN NSUKKA METROPOLIS SOUTH EASTERN NIGERIA

Abstract: to combat food insecurity and malnutrition among the local populace. However, the giant rat has been reported to harbour many parasites thus, its close association with man in raising them as mini-livestock and the consumption of the meat could be a public health risk to individuals handling them. This study was conducted to investigate the gut parasites and their prevalence on African giant rat in Nsukka metropolis. A total of 21 giant rats comprising 13 males and 8 females were trapped for the study. The gia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Moreover, parasites, as potential pathogens, constitute a burden to wildlife and domestic animal because of the physiological distress and mechanical injuries they cause to animals [ 29 ]. The work of Graber et al [ 30 ] in Chad and the Central African Republic on the helminths of some wild artiodactyls belonging to the Bovidae and Suidae families showed that the trematodes Fasciola gigantica and Paramphistomum sp. are specific parasites of ruminant bovids such as antelope and duiker.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, parasites, as potential pathogens, constitute a burden to wildlife and domestic animal because of the physiological distress and mechanical injuries they cause to animals [ 29 ]. The work of Graber et al [ 30 ] in Chad and the Central African Republic on the helminths of some wild artiodactyls belonging to the Bovidae and Suidae families showed that the trematodes Fasciola gigantica and Paramphistomum sp. are specific parasites of ruminant bovids such as antelope and duiker.…”
Section: Discussionmentioning
confidence: 99%